TECHNOLOGY FOR THE DEVELOPMENT OF SOCIAL COMPETENCIES RELATED TO FOLK CRAFTS - Esanova Sarvinoz Uktamovna (Bright Mind Publishing, 2025)
This article explores innovative pedagogical technologies aimed at developing students’ social competencies through engagement with traditional folk crafts. The study emphasizes the cultural, educational, and social significance of folk craftsmanship in shaping individual and collective identity. By integrating practical activities with interdisciplinary learning approaches, the proposed methods foster creativity, collaboration, and appreciation of national heritage. The article also discusses the role of educational institutions in promoting these competencies and presents recommendations for effectively incorporating folk crafts into the learning process.
Keywords: Folk crafts, social competencies, traditional heritage, educational technology, interdisciplinary approach, national culture, creative skills, pedagogical innovation.